2021
DOI: 10.3390/cancers13122903
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptomic Analysis Reveals Distinctive Molecular Traits and Novel Subtypes of Collecting Duct Carcinoma

Abstract: Collecting duct carcinoma (CDC) is a rare and highly aggressive kidney cancer subtype with poor prognosis and no standard treatments. To date, only a few studies have examined the transcriptomic portrait of CDC. Through integration of multiple datasets, we compared CDC to normal tissue, upper-tract urothelial carcinomas, and other renal cancers, including clear cell, papillary, and chromophobe histologies. Association between CDC gene expression signatures and in vitro drug sensitivity data was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The identification of these distinct subtypes and their transcriptomic traits provides the rationale for patient stratification and alternative therapeutic approaches. These insights could lead to rationalize the use of targeted therapies or immunotherapy for rare tumors according to the individual genomic alterations harbored [36]. Genetic and cytogenetic alterations in ncRCC aressumarized in Table 1.…”
Section: Collecting Duct Carcinomamentioning
confidence: 99%
“…The identification of these distinct subtypes and their transcriptomic traits provides the rationale for patient stratification and alternative therapeutic approaches. These insights could lead to rationalize the use of targeted therapies or immunotherapy for rare tumors according to the individual genomic alterations harbored [36]. Genetic and cytogenetic alterations in ncRCC aressumarized in Table 1.…”
Section: Collecting Duct Carcinomamentioning
confidence: 99%
“…Recently Gargiuli et al. ( 27 ), through integration of multiple datasets, compared cdRCC to UTUC, others RCC and normal tissue. The authors showed that cdRCC was characterized by a distinctive transcriptional program linked to the principal cells of the collecting ducts providing evidence that supports this origin and suggested at least two molecular subtypes of cdRCC distinguished by cell signaling, metabolic and immune-related alterations.…”
Section: Molecular Landscape Of Cdrccmentioning
confidence: 99%
“…On the other hand, the downregulated genes were linked to biological oxidations, amino acid metabolism, cell-cell communication, cellular response to external stimuli and G-protein coupled receptors (GPCR). Through the analysis of cancer cell line pharmacogenomics datasets, the authors showed that the gene-signature was predictive of higher sensitivity to some therapeutics options as tyrosine kinase inhibitors, SRC and MAPK signaling inhibitors ( 27 ).…”
Section: Molecular Landscape Of Cdrccmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an integrative transcriptomic study of 17 CDC patients identified that CDC may originate from the distal convoluted tubules of the nephron. Moreover, CDC is considered not only a metabolic disease but also an oxidoreductase activity and pyruvate metabolism [ 16 ]. These studies have mainly focused on Western populations, whereas the genomic profile of CDC patients in the Chinese population remains unclear.…”
Section: Introductionmentioning
confidence: 99%